2016
DOI: 10.1139/cjes-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Neo-Tethys geodynamics and mantle convection: from extension to compression in Africa and a conceptual model for obduction

Abstract: Since the Mesozoic, Africa has been under extension with shorter periods of compression associated with obduction of ophiolites on its northern margin. Less frequent than “normal” subduction, obduction is a first order process that remains enigmatic. The closure of the Neo-Tethys Ocean, by the Upper Cretaceous, is characterized by a major obduction event, from the Mediterranean region to the Himalayas, best represented around the Arabian Plate, from Cyprus to Oman. These ophiolites were all emplaced in a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 139 publications
(205 reference statements)
5
74
0
Order By: Relevance
“…This event is known everywhere in the northern part of Africa as the "Santonian Event" We st L ig u r ia n T e t h y s , 2005). It is also known in Europe (among others, Kley and Voigt, 2008;Jolivet et al, 2016; with references therein). Nonetheless, its effects remain weak or overprinted by subsequent events in the Tell-Rif.…”
Section: The First Tectonic Inversions Of the Southernmentioning
confidence: 99%
“…This event is known everywhere in the northern part of Africa as the "Santonian Event" We st L ig u r ia n T e t h y s , 2005). It is also known in Europe (among others, Kley and Voigt, 2008;Jolivet et al, 2016; with references therein). Nonetheless, its effects remain weak or overprinted by subsequent events in the Tell-Rif.…”
Section: The First Tectonic Inversions Of the Southernmentioning
confidence: 99%
“…The main observation from these maps is that the extended and thin lithosphere of East and Southeast Asia lies over the leading edge of the southeastward lithospheric flow (Figures and ). This situation is reminiscent of the evolution of the African Plate since the Paleozoic with the rifting and detachment above the northward mantle flow of continental ribbons that then crossed the Tethys Ocean until they finally collided with the southern margin of Eurasia (Jolivet et al, ).…”
Section: Lithospheric Thicknessmentioning
confidence: 99%
“…Yet we know that different styles of convection may have significant consequences for the dynamics of mountain belts. For instance, whether slabs enter the lower mantle or not leads to orogens controlled by slab‐pull or slab suction and the transition between the two styles of subduction can lead to large‐scale obduction (Faccenna, Becker, Conrad, et al, ; Faccenna, Becker, Jolivet, et al, ; Husson et al, ; Jolivet et al, ). Although it was shown that the mantle flow induced by slab retreat is able to impose shearing conditions at the base of the overriding plate and controls deformation in the back‐arc region (Capitanio, ; Capitanio et al, ; Chen et al, ; Faccenna et al, ; Jolivet et al, ; Menant, Sternai, et al, ; Sternai et al, ), at larger scale, few tectonic models explain crustal deformation considering a possible drag by underlying currents (Conrad & Lithgow‐Bertelloni, ; Ghosh et al, ; Koptev et al, , ; Stoddard & Abbott, ).…”
Section: Introductionmentioning
confidence: 99%
“…The push of the mantle plume impinged at the base of the African plate triggering local extension is shown to be sufficient for microblock separation. The presence of a continuous external push (possibly resulting from a large-scale mantle flow due to the large plume postulated by Jolivet et al, 2016) is shown to be indispensable to sustain continental subduction of the separated microblock (compare Figures 5a-5c and 5d). In contrast, variations in plume temperature do not appear to be crucial (models 2-3; Figures 3b and 3c).…”
Section: Discussionmentioning
confidence: 92%